Cumulative Antibiotic Use Significantly Decreases Efficacy of Checkpoint Inhibitors in Patients with Advanced Cancer. (10th July 2019) - Tinsley, Nadina; Zhou, Cong; Tan, Grace; Rack, Samuel; Lorigan, Paul; Blackhall, Fiona; Krebs, Matthew; Carter, Louise; Thistlethwaite, Fiona; Graham, Donna; Cook, Natalie
Abstract: Background: With the advent of immunotherapy, substantial progress has been made in improving outcomes for patients with advanced cancer. However, not all patients benefit equally from treatment, and confounding immune‐related issues may have an impact. Several studies suggest that antibiotic use (which alters the gut microbiome) may result in poorer outcomes for patients treated with immune checkpoint inhibitors (ICI). Materials and Methods: This is a large, single‐site retrospective review of n = 291 patients with advanced cancer treated with ICI ( n = 179 melanoma, n = 64 non‐small cell lung cancer, and n = 48 renal cell carcinoma). Antibiotic use (both single and multiple courses/prolonged use) during the periods 2 weeks before and 6 weeks after ICI treatment was investigated. Results: Within this cohort, 92 patients (32%) received antibiotics. Patients who did not require antibiotics had the longest median progression‐free survival (PFS), of 6.3 months, and longest median overall survival (OS), of 21.7 months. With other clinically relevant factors controlled, patients who received a single course of antibiotics had a shorter median OS (median OS, 17.7 months; p = .294), and patients who received multiple courses or prolonged antibiotic treatment had the worst outcomes overall (median OS, 6.3 months; p = .009). Progression‐free survival times were similarly affected. Conclusion: This large, multivariate analysis demonstrated that antibiotic use is an independent negative predictor of PFS and OS in patients with advanced cancer treated with ICIs. This study highlighted worse treatment outcomes from patients with cumulative (multiple or prolonged courses) antibiotic use, which warrants further investigation and may subsequently inform clinical practice guidelines advocating careful use of antibiotics. Abstract : Evidence suggests that antibiotic use may result in worse outcomes for patients treated with immune checkpoint inhibitors. This article assesses the effect of including cumulative antibiotic use, at the time of ICI treatment, on outcomes for patients with advanced or metastatic solid tumors.